Competency‐based clinical pharmacogenomics activities during an advanced pharmacy practice experience. Issue 1 (26th November 2020) - Cicali, Emily J.; Cook, Kelsey J.; Arwood, Meghan J.; Elchynski, Amanda; Wiisanen, Kristin
Abstract: Introduction: Clinical pharmacogenomics is a required element in the Doctor of Pharmacy (Pharm.D.) curriculum. However, pharmacogenomics is not widely adopted into clinical practice and as such, considerable variability in clinical teaching and learning activities within pharmacogenomic advanced pharmacy practice experiences (APPE) exist. Among other places in the University of Florida's Pharm.D. curriculum, practical applications of clinical pharmacogenomics are covered during the APPE year through an elective 6‐week Clinical Pharmacogenomics APPE. Objectives: Describe our analysis of clinical pharmacogenomics competency statements and our process of matching these statements with learning activities in our APPE to: (a) identify unmet needs, and (b) identify essential activities for a clinical pharmacogenomics APPE for students to meet pharmacogenomics competencies. Methods: We reviewed previous APPE syllabi to identify APPE activities, conducted a literature search to identify recommendations on clinical pharmacogenomics competencies, and then aligned these two components. A gap analysis was conducted by preceptors to determine the need for additional activities. Results: Twenty APPE activities and 42 competency statements were identified. Eighty‐six percent of competency statements were matched to one or more APPE activities. Three activities were added to our Clinical Pharmacogenomics APPE. Conclusion: We refined our Clinical Pharmacogenomics APPE to ensure students meet all of the identified competency statements and provided an essential list of APPE activities that, if implemented, will meet these competency statements.